Color Psychology on Book Covers: An Analysis of Visual Preferences Across Adult and Children’s Books for Enhanced Audience Targeting at Sampoerna Academy Grand Pakuwon Surabaya - Arum Karisma Nadya Lashita; Imam Yuadi (Jurnal Ilmu Perpustakaan, 2026)
Book covers play a crucial role in capturing readers’ attention and shaping initial perceptions, making color an essential element in influencing emotional engagement and guiding audience targeting across children’s and adult literature. Color functions as a visual communication tool that reflects the tone, theme, and intended readership, while also aligning with psychological and developmental preferences. The objective is to identify how color attributes such as brightness, saturation, and dominant hues differentiate book categories and support effective visual classification. A quantitative content analysis approach is applied using 6,093 book cover images collected from the Sampoerna Academy Library. Data extraction is conducted using Python libraries, including OpenCV and NumPy, to measure RGB (Red, Green, Blue), HLS (Hue, Lightness, Saturation), and colorfulness attributes. The analysis is supported by visualization techniques such as Scatter Plot and Radial Visualization (RadViz) through Orange software to explore relationships between color variables and book categories. The results reveal clear visual distinctions between the two categories. Children’s book covers predominantly appear in higher brightness and color intensity ranges, with strong associations to warm and vibrant hues such as red, yellow, and orange. In contrast, adult book covers are more widely distributed across lower brightness levels and are associated with cooler and more subdued tones such as blue, green, and purple. Some overlap is identified, indicating that certain colors can function across categories depending on context. The findings confirm that color attributes serve as reliable indicators for audience targeting and visual classification. Future research is recommended to integrate additional design elements, including typography and layout, to provide a more comprehensive understanding of book cover design.